2010
DOI: 10.1152/jn.00912.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Contribution of Area 5 of the Posterior Parietal Cortex to the Planning of Visually Guided Locomotion: Limb-Specific and Limb-Independent Effects

Abstract: We tested the hypothesis that area 5 of the posterior parietal cortex (PPC) contributes to the planning of visually guided gait modifications. We recorded 121 neurons from the PPC of two cats during a task in which cats needed to process visual input to step over obstacles attached to a moving treadmill belt. During unobstructed locomotion, 64/121 (53%) of cells showed rhythmic activity. During steps over the obstacles, 102/121 (84%) of cells showed a significant change of their activity. Of these, 46/102 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 96 publications
6
66
0
Order By: Relevance
“…Several studies have reported that gaze is normally directed about two step lengths ahead during walking behaviour in humans [23,26] and cats [24,25], and subjects are better able to step over a single obstacle in their path when they become visible two steps in advance [46]. In addition, certain neurons in area five of the posterior parietal cortex in cats show an increase in activity two to three steps prior to stepping over an obstacle [47]. However, no explanation has been offered for what is special about this distance.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that gaze is normally directed about two step lengths ahead during walking behaviour in humans [23,26] and cats [24,25], and subjects are better able to step over a single obstacle in their path when they become visible two steps in advance [46]. In addition, certain neurons in area five of the posterior parietal cortex in cats show an increase in activity two to three steps prior to stepping over an obstacle [47]. However, no explanation has been offered for what is special about this distance.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen subjects [5 females, 9 males; mean age = 18.7 (18)(19)(20)(21) years] participated in experiment 1, 18 subjects [7 females, 11 males; mean age = 19.1 (18)(19)(20)(21) years] participated in experiment 2, and 12 subjects [5 females, 7 males; mean age = 20.0 (18)(19)(20)(21)(22) years] participated in experiment 3. Data from two subjects in experiment 1 were excluded because their average stepping accuracy across all conditions was more than 2 SDs from the mean.…”
Section: Methodsmentioning
confidence: 99%
“…This area has been implicated in the control of reaching to remembered locations in primates (24,25) and may play an analogous role in stepping behavior during locomotion. In vivo recordings from cats walking on a treadmill revealed that neurons from this region increase their firing rates in the 2-3 steps before the step over an obstacle (22), suggesting that this area could be involved in encoding the position of upcoming obstacles relative to the moving observer. This estimate may then be used by the motor cortex to generate the descending signals that modulate the activity of synergistic muscle groups in the limbs to enact the gait adjustment necessary to account for the upcoming obstacle (or target foothold) (23).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Precuneus, parahippocampal cortex, hippocampus, and lingual gyrus have been shown to be involved in cognitive aspects of movement in space (Rosenbaum et al, 2004;Epstein, 2008;Schinazi and Epstein, 2010;Wegman and Janzen, 2011;Drew and Marigold, 2015). Based on animal studies, some of these regions appear to be critical for coordinating motor activity during complex motor tasks involving object avoidance, which may involve control of foot placement and toe muscle activity (Andujar et al, 2010).…”
Section: -130mentioning
confidence: 99%